RETRAINING NEEDS OF MOTOR VEHICLE MECHANICS TEACHERS AT TECHNICAL COLLEGE LEVEL - Audu, Rufai; Musta'amal, Aede Hatib Bin; Kamin, Yusri Bin; Saud, Muhammad Sukri Bin; M. M., Inti (Journal of Technical Education and Training, 2014)
The study is designed to identify the areas of retraining needed by Motor Vehicle Mechanics (MVM) teachers in technical colleges in Niger State and Federal Capital Territory (FCT) Abuja, Nigeria. Two research questions were used to guide in the conduct of the study. The teachers of MVM program in the technical colleges in Niger State and FCT Abuja Nigeria constitute the respondents of the study. A 35 item questionnaire was used to collect data for the study. The data was analyzed using frequency counts, mean and standard deviation. The analysis of the data revealed that MVM teachers in the technical colleges needs retraining in terms of pedagogical skills as well as practical skills areas in MVM Base on the finding the following recommendations were made; immediate retraining for the MVM teachers in the technical colleges with emphasis in the areas of pedagogical and technical skills. There should be collaboration between the technical colleges and the industries to enable the MVM teachers to acquire the needed skills to impart to the learners so that upon graduation the students can be employable to contribute to the development of their immediate society and the nation at large.